Stress tests, labor demand, and the dynamic adjustment of private firms - Kali, Raja; Liu, Andrew Yizhou (Journal of Banking & Finance, 2026)
We show that the Dodd-Frank Act stress tests worsened bank loan terms and reduced vacancy postings by 16% among private firms with prior relationships with stress-tested banks. The decline is concentrated in postings for less-educated workers, indicating a contraction in hiring along this margin. These effects are temporary. Firms respond to tighter credit by shifting toward smaller financial institutions. This adjustment increases loan sizes from both new and existing lenders, which mitigates the impact of stress tests on labor demand over time.